Pengaruh Aksesibilitas, Amenitas, Dan Atraksi Wisata Terhadap Minat Kunjungan Wisatawan Ke Wahana Air Balong Waterpark Bantul Daerah Istimewa Yogyakarta - Leylita Novita Rossadi; Endang Widayati (Journal of Tourism and Economic, 2018)
This study aims to determine the effect of marketing mix on purchasing decisions at PT. Tunas Indonesia Tours & Travel Yogyakarta branch. Marketing mix variables consist of 4 sub variables namely: Price (X1), Product (X2), Promotion (X3), and Place (X4). The population in this study is consumers who make purchases at PT. Tunas Tours & Travel Yogyakarta in 2016. Using non-random sampling method with purposive sampling technique with a sample of 100 respondents. In this study using is descriptive and quantitative using multiple linear regression method. The results showed that price and location / distribution variables have a positive and significant influence on purchasing decisions. This is shown from the results of multiple linear regression test where both variables have P value <of 5% and t arithmetic> t table. While the product and promotion variables have an insignificant effect on purchasing decisions. This is shown from the results of multiple linear regression test of these variables have a value of P value> of 5% significant. The test results simultaneously, show the marketing mix has a significant influence in purchasing decisions where the test results proved P value <of 0.05 or 5%